Economic Impact Analysis of Sea Toll Program Implementation in Eastern Indonesia: A Review in Papua, Maluku, and East Nusa Tenggara Regions - Robby Kurniawan; Sudjanadi Tjipto Sudarmo; Edi Abdurachman (Dinasti Research, 2024)
The Sea Toll is a form of transportation development policy in support of the government's development policy direction, especially as an embodiment of the third axis of Indonesia's policy agenda as the world's maritime axis, namely prioritizing infrastructure development and maritime connectivity. The lagging development in the eastern region of Indonesia has its own relevance for the important role of the Sea Toll program.This research aims to analyze the implementation of the Sea Toll program in order to support development in the Papua, Maluku and East Nusa Tenggara regions and analyze the economic impact on these three regions. This research uses a post-positivist paradigm. This study uses a qualitative and quantitative approach (mixed method) with a post-positivist paradigm. The data sources for this study consist of primary and secondary data sources. Primary data sources come from interviews, observations, and surveys. The secondary data sources are in the form of document studies. The data was analyzed using qualitative and quantitative data analysis techniques. In qualitative data analysis techniques, this study follows the Miles and Huberman model data analysis method. As for quantitative data analysis techniques, this study applies Results Chain Method adopted Partial Least Square (PLS) analysis using Smart PLS software. The research results show that the Sea Toll policy can still have an economic impact both directly and indirectly. The implementation of the sea toll has a direct impact on the transportation sector but not yet optimal to have a work impact. In addition, the implementation of sea tolls also has an indirect impact on other economic sectors, but has not been able to contribute to the increase in taxes or regional revenue.